A study of relationship between organizational culture and employee’s job performance among non-academic staff at Universiti Teknologi MARA, Malacca Campus - Hasbullah, Hasmawati; Fadzlon, Nazriah (2006)
Organizational culture has been practices in most of the organization. It is cognitive framework consisting of attitudes, values, behavioral norms and expectations shared by organization members. While employees’ job performance is the degree of accomplishment of the tasks that make up an employee’s job. It reflects how well an employee is fulfilling the requirements of a job. We have done the research at Universiti Teknologi MARA, Malacca Campus. We choose Universiti Teknologi MARA, Malacca Campus because it is one of the branch campuses of Malaysia’s premier institution of higher learning that has experienced a phenomenal growth since its inception in 1956. Universiti Teknologi MARA, Malacca Campus was fully operated at permanent campus in Lendu, Alor Gajah since January 1994. In this research, we will focus on “The Relationship between the Organizational Culture and the Employees’ Job Performance among Non-Academic Staff in Universiti Teknologi MARA, Malacca Campus”.